The locative syntax of Experiencers. The case study of phraseological units as psych-predicates - Anna Dąbrowska (LingBaW)
The name psych-verbs is commonly assigned to verbs denoting mental or emotional states, such as fear, worry, frighten, or surprise. Such verbs select a participant/an individual who experiences an emotional or mental state, usually referred to as an Experiencer, and a non-Experiencer argument, sometimes called stimulus, trigger of emotion, causer or target/subject matter, or subsumed under the label of ‘theme’ (Landau, 2010, p. 5). The special behaviour of Experiencers, related to the so-called ‘psych effects’, is the reason why psychological predicates have been a subject of debate in theoretical syntax for several decades.